The role and place of ethnoarchaeology in current archaeological debate - Politis, Gustavo Gabriel (2016)
One characteristic of ethnoarchaeology is that it is a field in a constant state of reflection, not only about its ontological and epistemological bases, but also about the usefulness of its results and the ethical dimension of its practice. The four papers which comprise this special section of WorldArchaeology are in consonance with this reflexive state. These papers approach different current issues in ethnoarchaeology from different perspectives and represent the vitality and worth of this (sub-)discipline.Although I find the paper by Lyon and Casey extremely illuminating, and I agree with most of their ideas, I am not convinced that ethnoarchaeology is a methodology. More in agreement with the papers by Cunningham and MacEachern and that by Sillar and Ramón Joffré, I believe that it is either a discipline (or an "ambiguous sub field", as the former authors call it) between archaeology andethnography, or a research strategy framed within different theoretical structures (from behavioural ecology to the ?ontological turn?), displaying a variety of methods (from participant observation to the development of sophisticated software) and applying many recording techniques (from simplemaps drawn with a pencil to highly sensitive Global Positioning System mapping).